Distribution of 11 beta-hydroxysteroid dehydrogenase along the rabbit nephron. - Bonvalet, J P (1990)
It has been recently proposed that 11 beta-hydroxysteroid dehydrogenase (11 beta-OHSD) is responsible for aldosterone tissue specificity. A 11 beta-OHSD deficiency has been invoked as a cause of the syndrome of apparent mineralocorticoid excess, and 11 beta-OHSD inhibition by liquorice has been invoked to explain the hypertension induced by this drug. Since the renal tubule is composed of aldosterone-sensitive and insensitive segments, we determined the distribution of 11 beta-OHSD along the rabbit tubule. Pools of tubular segments isolated by microdissection were incubated for 2 h at 37 degrees C in the presence of [3H]corticosterone (3H-B, 8.10(-9) M). Afterwards, the amounts of 3H-B and of the metabolite 11-dehydrocorticosterone (3H-A) were determined using HPLC analysis. In the proximal tubule, in either its convoluted or straight portion, and in the medullary thick ascending limb, the amount of 3H-A was 19.6 +/- 3.8% (n = 12), 17.9 +/- 3.4 (n = 8), and 15.0 +/- 2.2 (n = 4), respectively, of the sum of 3H-A + 3H-B. In the cortical ascending limb and the collecting tubule in its cortical and medullary parts, it was 74.7 +/- 6.8% (n = 4), 74.1 +/- 4.9 (n = 9) and 64.6 +/- 14.1 (n = 3), respectively. In both proximal and cortical collecting tubule, addition of carbenoxolone 8.10(-4) M, an inhibitor of 11 beta-OHSD, almost completely inhibited the conversion of 3H-B to 3H-A. Thus, 11 beta-OHSD activity was high in the aldosterone-sensitive segments, and low in the aldosterone-insensitive segments. These results strongly favor the hypothesis that 11 beta-OHSD is a key enzyme in mineralocorticoid tissue specificity along the rabbit nephron. They reinforce the notion that a defect in 11 beta-OHSD plays a major role in the syndrome of apparent mineralocorticoid excess and liquorice-induced hypertension.